Comparison of the efficacy of HoLEP and TURP in the treatment of elderly benign prostatic hyperplasia patients: a retrospective study - Aizezi, Xierzhati; Feng, Liancheng; Wang, Zheng; Ma, Yuan; Li, Jifu; Keremu, Abuduweili; Rouzi, Maihemujiang; Dilixiati, Ailiyaer; Wang, Beiping; Shi, Hanzhen; Huang, Jinxing (Aktuelle Urologie, 2024)
To prove that holmium laser prostatectomy (HoLEP) is safe and effective in the treatment of benign prostatic hyperplasia (BPH), and is superior to transurethral prostatectomy (TURP) for elderly patients.We retrospectively studied 565 HoLEP patients and 76 TURP elderly patients. HoLEP patients were first divided into three groups according to their age(Under 65 years old group, 65–79 years old group and over 80 years old group), and their preoperative, intraoperative, and postoperative characteristics were then compared. Secondly, the same characteristics of HoLEP and TURP patients over 80 years were compared. Chi-square test, one-way ANOVA and Fisher’s exact test were used in this study.Firstly, we compared HoLEP patients in different age groups and found that there was statistically significant difference in diabetes, CCVD and bladder stones, among the three groups (P<0.05).Secondlye, we compared HoLEP and TURP treatments in elderly patients (≥80 years old). The patients with HoLEP had a higher share of diabetes, CCVD and anticoagulation (P<0.05). Moreover, compared with TURP patients, HoLEP patients had shorter enucleation duration, more enucleate prostate weight, fewer hemoglobin diminutions, shorter bladder irrigation time, shorter catheter-indwelling period, and shorter hospital period (P<0.05). Although there was no difference in IPSS, Qmax and QOL between the two groups before operation (P>0.05), the difference was statistically significant, 6 months after the operation (P<0.05).HoLEP is safe and effective for BPH patients, and is superior to transurethral TURP for elderly patients.
Keywords: BPH; HoLEP; TURP